Special tax supervision as an element of protection of budget revenues (Discourse of Law and Administration, 2025)
This article discusses the issue of special tax supervision, its origins and currently applicable solutions. Attention was drawn to the decomposition of this institution, in particular the departure from standardizing this concept. The focus was on the functional importance of fiscal supervision, special tax supervision, and currently ad hoc and permanent customs and fiscal control. Due to the supervision of the production of excise goods, these institutions were intended to ensure the correctness of the production process, but also to ensure the correct settlement of excise tax, so despite changes in the nomenclature, their functional meaning remained the same.
Keywords: excise duty; budget; tax supervision; special tax supervision